Unidos pelo controle: uma etnografia das práticas de sociabilidades dos cyberatletas do futebol digital - Valentim, Daniel Costa (2012)
The emergence of electronic games that simulate soccer matches in technologically supported media called "video games" is presented as the main trigger of practices of sociability of a group of people in the city of Fortaleza and other cities of Brazil. It was then possible to observe the realization of a complex network of championships, and the emergence of a new class of agents who define themselves as “cyber athletes” or " professional digital soccer players”. These agents are distinguished by effusive and intense participation in offline digital soccer tournaments. In mid 2005, these players began a process of professionalization of the practice that led to the formalization of various associations and federations of players in different Brazilian states. In Fortaleza, these agents were the formalization of an institution called Federação Cearense de Futebol Digital (FCeFD). The advent of these institutions enabled us to notice the emergence of a market of symbolic goods originated among the intensive practice of these athletes in this network of championships that we call "circuit of the cyberathletes". In this dissertation, we developed an ethnography of the practices of sociability of the agents in question through this frenetic search for these signs of distinction present in the field of digital soccer.